Por um despertar antropológico no interior das instituições estatais: formas de ser e fazer do antropólogo-agente público a partir da experiência de gestão dos jogos dos povos indígenas de Minas Gerais - Aline Galantinni Silva (2020)
Based on an auto-ethnographic proposal in the management of the Indigenous Peoples Games of Minas Gerais-JPIs, the present study proposes to explore possible paths for the conscious performance of anthropologists who are in the situation of state public agents. The study seeks to demonstrate how the anthropologist, recognizing himself as such, can find ways within his professional context, to contribute to a transformation in state public policies related to indigenous peoples. Throughout the study, it is evident how the state logic is articulated in order to perpetuate a crisis situation, as a permanent and constant process in the daily lives of Indigenous Peoples, preventing their full access to public policies in general, notably, sports. The JPIs of Minas Gerais who, since their conception, already experience the experience of exclusion, due to their de-identification with the proposal of the National JPIs, are still excluded from state public sports policies, with indigenous peoples unable to develop the match from from their own perspectives. As disheartening as this scenario appears, this study seeks to defend that the contribution of the anthropologist as a state public agent, even if it does not directly imply decision-making levels, initiates a reflective process, an “opening of minds” within state organizations through their public agents who are responsible for the daily conduct of public policies.